Upaya Meningkatkan Kebugaran Jasmani melalui Permainan Gobak Sodor pada Siswa Mts - Taufiq Firmansyah; Arief Nur Wahyudi; Kartika Septianingrum (CV Edujavare Publishing, 2024)
This study aims to identify student activity through the use of the traditional game of gobak sodor in improving fitness in class VII B MTS Ma'arif Tempursari. The second objective is to evaluate the results of the game of gobak sodor in an effort to improve student fitness in the same class. The method used in this study is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of two cycles with the stages of planning, implementation, observation, and reflection. The research instrument used was a student fitness test through a 2.4 km run using the Indonesian Physical Fitness Test (TKJI) for ages 12-13 years. The results showed an increase in student learning completeness from cycle I to cycle II, with the percentage increasing from 67.1% to 83.5%. The use of the game of gobak sodor has also been proven to provide positive results in improving student fitness, as reflected in the increase in student success rates from cycle to cycle. Thus, it can be concluded that the use of the game of gobak sodor is effective in improving student fitness in PJOK learning, especially on the topic of physical fitness.